(untitled) (World Bulletin of Social Sciences, 2024)
Building Information Modeling (BIM) is transforming the architecture, engineering, and construction (AEC) industry, yet its adoption remains challenging due to varying definitions and applications. This paper explores the historical evolution of BIM, examining key contributors and terminologies while highlighting its theoretical underpinnings and practical benefits. Emphasis is placed on its distinctions from CAD systems, sociological impacts, and its pivotal role in enhancing collaboration among project teams. The research provides a comprehensive review of literature and expert opinions, presenting BIM as both a process and a model that fosters precision, efficiency, and innovation throughout a building’s lifecycle. Key principles for effective BIM implementation are also discussed, along with recommendations for improving adoption and integration in the AEC industry